ANALISIS IMPLEMENTASI PELAPORAN KEUANGAN SEKOLAH SEBAGAI INSTRUMEN TRANSPARANSI DAN AKUNTABILITAS PUBLIK DI SMP LABSCHOOL 1 UNESA SURABAYA - Sara Zakiyyatul Umma; Ilyas Adi Saputra; Ahmad Makhasin As Shufi; Haikal Ali Mu'tasim Billah; Adinda Islamatul Nur Aziza; Ima Widiyanah (STKIP Subang, 2026)
Financial management in educational institutions plays a crucial role in maintaining smooth school operations while supporting improvements in the quality of learning. This study aims to interpret the implementation of financial reporting as a means of transparency and public accountability at SMP Labschool 1 UNESA Surabaya, as well as to identify obstacles and corrective measures. The approach used was descriptive qualitative through direct observation, interviews with the principal and treasurer, and analysis of the RKAS (Work Plan and Budget) documents and general ledger. The findings indicate that the school has implemented a systematic financial management system based on the Education Quality Report (Rapor Mutu Pendidikan) data in preparing the RKAS. School funds come from SPP (School Fees), central BOS (School Operational Assistance), and regional BOSDA (School Operational Assistance). Obstacles that emerged included human resources' lack of understanding of frequently changing accounting regulations, the risk of manual recording errors, and urgent needs not yet planned for in the initial budget. To address these issues, the school implemented budget efficiency measures, conducted regular monitoring by the foundation, and planned to digitize reporting to strengthen and maintain public trust.